A comparative study of sublingual versus oral misoprostol following oral mifepristone for second trimester termination of pregnancy - Gupta, Ruchi; Banerjee, Krishna Priya; Pant, Reena (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The objective of this study is to assess the effectualness and safety of sublingual versus oral misoprostol following oral mifepristone for second trimester termination of pregnancy. Methods: This institution based contingent study was conducted on 220 women requesting for mid-trimester termination of pregnancy between 12-20 weeks with legal indication as per Govt. MTP act. After excluding the women as per exclusion criteria, they were randomly allocated into two groups (Group A Sublingual, Group B Oral), the women received 200 mg oral mifepristone followed by sublingual or oral misoprostol 400µg three hourly for a maximum of 5 doses 48 hours later. The course of misoprostol was reiterated if women failed to abort in 24 hours. Results: The mean induction-abortion interval of Group-A and Group -B was 4.02±1.39 hours and 6.44±1.79 hours respectively. The mean dose of misoprostol in Group–A and Group-B was 680±220.4µg and 1003.6±274.9µg. Hence mean Induction-abortion interval and dose were shortened in Group-A as compare to Group-B (p <0.05). There was 100% success rate noticed via both routes. Evacuation was done in 4 (3.64%) women in Group-B as compare to only 1 (0.91%) in Group-A . The acceptability was significantly more in Group-B (100%) as compare Group-A (52.73%), probably because of unpleasant taste of sublingual misoprostol. All side effects (Nausea, pain, headache, and diarrhea) were common in both the Groups, only fever was significantly more common in sublingual group as compare to oral group (p<0.05). Conclusions: From present study authors conclude that, sublingual misoprostol when combined with mifepristone is effective for medical abortion in second trimester in terms of effectualness, endurability and success rate than oral route.